Audit, Accounting, and Finance Training for Management Trainees of PT HSBC Jakarta - Wiwiek Mardawiyah Daryanto (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2021)
Accounting is an information service related to all of the activities in the organization, such as operating activities, financing activities, and investing activities. And in all of the activities the emphasis is on using accounting information in the process of making decisions based on financial reports. The financial reports are the result of the accounting process. One related discipline is auditing, which can be defined as the process of examining and evaluating a company's financial statements through an independent auditor. In addition, accounting is used to support the management for internal decision making, or called management accounting. To understand the importance of accounting, Sekolah Bisnis dan Manajemen – Institut Teknologi Bandung (SBM-ITB) in collaboration with PT HSBC, Jakarta, Indonesia conducted General Banking Training on March 22-26, 2021. The training consists of nine (9) topics, including Auditing, Accounting and Finance and is held on March 23, 2021. The speakers of the training are several academicians, including the author. The method used in the training is online lecturing and discussion combined with case studies. We also conducted pre and post-tests to ensure the result of the training. The participants are seven (7) new employees of PT HSBC recruited from various domestic and foreign universities. The results of the training showed that the participants improved their understanding on the importance and the use of accounting information based on pre and posttests. In addition, it showed an increase in value of 54% in the posttest. Further, the participants are satisfied and provide positive feedback of 4.14 out of 5. After observing the process, we consider that the training ran smoothly and effectively due to high interest and enthusiasm of the participants.